A Review on Chitosan Utilization in Membrane Synthesis. Issue 3 (7th June 2016) - Jafari Sanjari, Alireza; Asghari, Morteza
Abstract: Membrane separation technologies are very energy efficient and the general interest has drastically increased over the last decade. Biopolymers as membrane compounds have gained increased attention due to their renewability. Chitosan is a derivative of chitin, the second most abundant biopolymer and shows many advantages required for a membrane. This article provides an overview of recent progress on the application of chitosan membranes. The applications include gas separation, direct methanol fuel cells (DMFCs), pervaporation, water treatment (heavy metal and dye removal, salt rejection), and the biomedical field. The preparation of different chitosan membranes is presented as well as its capabilities in the different fields of application. Abstract : In this review, recent advances in the application of chitosan membranes were discussed. Chitosan membranes show the benefit of low energy cost, ease of operation and, also owing to its hydrophilicity, biocompatibility, ease of modification, etc. They have been widely applied to several applications including gas separation, DMFC, pervaporation, and water treatment.